Życie rodzinne rodziny Morawskich we wspomnieniach Azi z Morawskich Umiastowskiej - Szafer, Katarzyna (Wydawnictwo Naukowe UAM, 2002)
Jadwiga Morawska-Umiastowska wrote the memoirs in which she showed her landed gentry family life at the turn o f 19lh century. These memoirs are very interesting for a historian and sociologist, because they help to research the functions of family. In the article there are a few of them, but show members of the Morawski family in different roles and perspective.
The family life of the Morawski family in the memoirs of Azia neé Morawska Umiastowska